2(3x-2)=5(2x+1)=x-4

Simple and best practice solution for 2(3x-2)=5(2x+1)=x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x-2)=5(2x+1)=x-4 equation:



2(3x-2)=5(2x+1)=x-4
We move all terms to the left:
2(3x-2)-(5(2x+1))=0
We multiply parentheses
6x-(5(2x+1))-4=0
We calculate terms in parentheses: -(5(2x+1)), so:
5(2x+1)
We multiply parentheses
10x+5
Back to the equation:
-(10x+5)
We get rid of parentheses
6x-10x-5-4=0
We add all the numbers together, and all the variables
-4x-9=0
We move all terms containing x to the left, all other terms to the right
-4x=9
x=9/-4
x=-2+1/4

See similar equations:

| 7x^2-49x-1=0 | | -6=3(5x-7)-3(7-x) | | 0=11+3x+x^2 | | 1/2m+7=3m-8 | | y2−4=-1 | | 12=7x-30 | | 0=9-12x+4x^2 | | Y=-4/3x-19 | | 4a+5=12 | | 0.5m+7=3m-8 | | 2y+10=8y-2 | | 10x-2+3x=11+4x-3 | | -12x+45=50 | | -1+8d=-129 | | -80=6(-8-4x)-4(6x+8) | | x2-16x+14=0 | | 7(n+4)=211 | | 5^-2x+5^3*5^2x=30 | | 7x-30=12 | | -80=6(-8-4n)-4(6n+8) | | -20u=-25 | | 2x2-9x=0 | | 5m-13=4 | | 69/50=x/100 | | 1/2.8x=104 | | -10k+10=-8k+6 | | 3w-4.8=4.4w-11.38 | | 1=2v−5 | | 1/3z=-5/6* | | 4-x÷12=-6 | | 5y+2y+1y=5y+2y+1y= | | 5x+8=29x-2 |

Equations solver categories